Study of Characteristics and Behavior of Beef Cattle Farmers in Badas Subdistrict, Kediri - Andaruisworo, Sapta; Solikin, Nur; Yuniati, Erna; Tanjungsari, Ardina; Anifiatiningrum, Anifiatiningrum (CV. Komunitas Dunia Peternakan, 2025)
The objective of this study was to examine the characteristics and behavior of beef cattle farmers in Badas Subdistrict, Kediri Regency, based on demographic factors. The research was conducted in the Badas Subdistrict area. This study utilized a qualitative descriptive approach using survey methods. The variables investigated were the characteristics and behavior of beef cattle farmers based on demographics, including gender, age, years of farming experience, education level, primary occupation, number of family dependents, livestock ownership, livestock ownership status, animal feed, timing of cattle sales, and location of cattle sales. The findings revealed that in Badas Subdistrict, Kediri Regency, all cattle farmers were male (100%). Most farmers were aged 46–55 years (57.76%), and 38.09% had more than 10 years of farming experience. The majority had completed junior or senior high school. The main occupation of 69.04% of farmers was farming. Most farmers had 1–2 dependents (50%) and owned more than 3 cattle. Livestock ownership was predominantly personal (64.28%). All farmers used agricultural waste as animal feed. Cattle were sold based on urgent needs, and 61.90% of farmers sold their cattle through intermediaries (blantik).